Emergence of linezolid-resistant coagulase-negative staphylococci in an intensive care unit. Issue 5 (3rd May 2016) - Balandin, Bárbara; Lobo, Beatriz; Orden, Beatriz; Román, Federico; García, Elena; Martínez, Rocío; Valdivia, Miguel; Ortega, Alfonso; Fernández, Inmaculada; Galdos, Pedro
Abstract: Background The aim of this study was to report the emergence of linezolid-resistant coagulase-negative staphylococci (CoNS) in an intensive care unit.Methods An observational study was conducted in critically ill patients with colonization or infection by linezolid-resistant CoNS between January 2010 and December 2014. We analyzed the epidemiological and clinical features, and the mechanism of resistance to linezolid. We also evaluated the association between the incidence of linezolid-resistant CoNS strains and the consumption of linezolid in the study period.Results During the study period 49 patients had a linezolid-resistant CoNS strain isolated from clinical samples (blood in 42 cases, urine in 6, peritoneal fluid in 1). Molecular study showed a combination of mechanisms of resistance. Most patients were critically ill (APACHE II score = 21.9 ± 8.3) and nearly all had undergone surgery and invasive procedures, and had prior exposure to antibiotics. Linezolid-resistant CoNS were considered to be contaminants in 42 patients and associated with infection in 7 patients, comprising bacteremia and septic shock in most of them. They were successfully treated with glycopeptides or daptomycin. A modest significant correlation was observed between the decrease in linezolid consumption and the lower incidence of resistant isolates.Conclusions Linezolid-resistant CoNS had emerged in critically ill patients with severe underlying diseases and prior antibiotic exposure. Most isolates represented colonization; however, linezolid-resistant CoNS can produce serious infections in critically ill patients. Glycopeptides and daptomycin seem to provide useful alternatives for therapy of these infections. A relationship was found between linezolid consumption and the incidence of linezolid-resistant CoNS strains.